2023
DOI: 10.1038/s41598-023-29804-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-municipality migration and spread of tuberculosis in South Africa

Abstract: Human migration facilitates the spread of infectious disease. However, little is known about the contribution of migration to the spread of tuberculosis in South Africa. We analyzed longitudinal data on all tuberculosis test results recorded by South Africa’s National Health Laboratory Service (NHLS), January 2011–July 2017, alongside municipality-level migration flows estimated from the 2016 South African Community Survey. We first assessed migration patterns in people with laboratory-diagnosed tuberculosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previously, we have shown that migration from an individual’s natal town has increased over the past two generations in the rural Northern Cape Province [ 31 ]. In addition, a recent longitudinal study leveraging data from South Africa’s National Health Laboratory Service showed that incorporating cross-municipality migration improves the ability to predict TB incidence [ 51 ]. For our “residence model”, we hypothesized that migrating from a rural to urban area in one’s lifetime increases the odds of active TB status due to greater exposure to M .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that migration from an individual’s natal town has increased over the past two generations in the rural Northern Cape Province [ 31 ]. In addition, a recent longitudinal study leveraging data from South Africa’s National Health Laboratory Service showed that incorporating cross-municipality migration improves the ability to predict TB incidence [ 51 ]. For our “residence model”, we hypothesized that migrating from a rural to urban area in one’s lifetime increases the odds of active TB status due to greater exposure to M .…”
Section: Resultsmentioning
confidence: 99%